2020
DOI: 10.5599/jese.744
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and quantum chemical parameters of (-)-(S)-9-flu¬oro-2,3-dihydro-3-methyl-10-(4-methyl-1-pipera-zinyl)-7-oxo-7H-pyrido[1,2,3-de]-1,4-benzoxazine-6-carboxylic acidas anti-corrosive agent for API 5L X-52 steel

Abstract: <p class="PaperAbstract">The inhibitive action of (-)-(S)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-7H-pyrido[1,2,3-de]-1,4-benzoxazine-6-carboxylic acid (Levaquin) on API 5L X-52 steel in 2 M HCl solution was investigated using potentiodynamic polarization method and quantum chemical study. Levaquin drug showed good inhibition efficiency of 88 and 95 % at 303 and 323 K, respectively. The results of experimental measurements revealed that Levaquin drug works as a mixed type inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The higher is the dipole moment of an inhibitor, the stronger is the dipole-dipole interaction of the inhibitor with metal surface, this also indicate that the dipole moment reflect in higher inhibition efficiency [46]. This discussion is in line with the present study, because all the calculated quantum chemical parameter values of this study given in Table 6, are within the acceptable range of values already reported for some excellent corrosion inhibitors [6,[43][44][45].…”
Section: Computational Chemistry Studysupporting
confidence: 90%
See 1 more Smart Citation
“…The higher is the dipole moment of an inhibitor, the stronger is the dipole-dipole interaction of the inhibitor with metal surface, this also indicate that the dipole moment reflect in higher inhibition efficiency [46]. This discussion is in line with the present study, because all the calculated quantum chemical parameter values of this study given in Table 6, are within the acceptable range of values already reported for some excellent corrosion inhibitors [6,[43][44][45].…”
Section: Computational Chemistry Studysupporting
confidence: 90%
“…The theoretical value of M for bulk metal is given as 7 eV, while ηM = 0 eV. Note also, that the electrophilicity index ( ) has recently been defined as [15,43,45]:…”
Section: Computational Chemistry Studymentioning
confidence: 99%
“…Thus, an increase in the E HOMO value facilitates adsorption of an inhibitor, while the energy of LUMO shows the potential of the molecule to accept electrons. [54][55] The energy gap can also be used to predict the inhibition efficiency of a compound or to develop a theoretical model for explaining the structure and confirmation barrier in many molecular systems. In the same vain, minimum values obtained from the energy gap E LUMO-HOMO gives a unique inhibition efficiency since the energy to displace an electron from the last occupied orbital will be reduced to the barest minimum.…”
Section: Theoretical Modellingmentioning
confidence: 99%